Technology Entrepreneurship Project (ENT 600) : Bite / Muhamad Alif Iman Mohamad Rodzi - Mohamad Rodzi, Muhamad Alif Iman (2021)
Bite is a newly develop company which produce and sell oral care product. Not common type of oral care product, the company focus on environment friendly and good health oral care product. The toothbrush made by bamboo tree that is easily biodegradable and unique toothpaste tablet that that made by organic chemical that good for health. Not only that, the whole process of producing the product is cleaner to environment and less harmful to health. The product packaging also focus on biodegradable material and reusable material. The company is founded by Lindsay McCormick. SWOT analysis have been done to analyst the product strength and weakness also opportunity and threat. The produce strength is that the product are environmental friendly product. While the weakness are competition from common oral product were already mass market and cheaper. The product opportunity is that the market of greener product has potential to growth in this decade where environment is huge issue. While threat are presence from well-known company that the product is common. Several key area need to be improve in order to gain market for the eco-oral care product.